Moving Borders. European Immigration Policy and the Multidimensional Instability of the Boundaries - Paolo Cossarini (Romanian Journal of European Affairs)
Two contemporary phenomena in the field of immigration force us to reflect upon the relationship between the migration flows and their political management: the tortuous development of the European immigration policies, and the contemporary struggles between member states in the administration and regulation of the last flows of immigrants coming from the 2011 “Arab Spring” countries. This paper attempts to answer two interrelated questions: What do these phenomena teach us about the features of the political and territorial space called Europe? Is it possible to read the current struggles on immigration as the essential political nature of Europe? Particular attention is paid to the agreement on migration among member states and European institutions and, at the same time, to the dimensions and dialectics of borders, with some examples from the Italian and Spanish cases. In this light, this paper aims to show how a wide theoretical and historical approach can be useful to understand the contradictory character of immigration policy and the multidimensional features of the EU borders.